Effect of heat stress on blood parameters in indigenous sheep (Journal of the Bangladesh Agricultural University, 2014)
The research was conducted to study the effect of heat stress on blood parameters in indigenous sheep. Nine sheep were divided into three groups which were almost similar in age, sex and weight. Three groups were divided as zero hour (T0), four hours (T4) and eight hours (T8) heat exposure to direct sunlight. During experimental period temperaturehumidity index (THI) value was calculated as 27.09 which indicate T4 and T8 groups were subjected to heat stress condition for at least four hours and eight hours respectively every day. The amount of red blood cell (RBC), hemoglobin (Hb%) and packed cell volume (PCV%) were increased significantly (p0.05) among the treatment groups. It can be concluded that heat stress had significant changes on some blood parameters in indigenous sheep. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21253 J. Bangladesh Agril. Univ. 12(1): 91-94, June 2014